2014
DOI: 10.3389/fpls.2014.00366
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death (PCD): an essential process of cereal seed development and germination

Abstract: The life cycle of cereal seeds can be divided into two phases, development and germination, separated by a quiescent period. Seed development and germination require the growth and differentiation of new tissues, but also the ordered disappearance of cells, which takes place by a process of programmed cell death (PCD). For this reason, cereal seeds have become excellent model systems for the study of developmental PCD in plants. At early stages of seed development, maternal tissues such as the nucellus, the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 77 publications
1
118
2
Order By: Relevance
“…The function of the nucellus in nonperispermic seeds is not yet clear. It was hypothesized that the nucellus degenerates in order to allocate its resources to embryo and endosperm development, which then become the primary nutrient storage compartments (Domínguez and Cejudo, 2014). Consistent with this hypothesis, we showed that Arabidopsis nucellus cells accumulate autophagosomes before undergoing cell death (Li and Vierstra, 2012).…”
Section: Developmental Progression Of Nucellus Degenerationsupporting
confidence: 74%
See 1 more Smart Citation
“…The function of the nucellus in nonperispermic seeds is not yet clear. It was hypothesized that the nucellus degenerates in order to allocate its resources to embryo and endosperm development, which then become the primary nutrient storage compartments (Domínguez and Cejudo, 2014). Consistent with this hypothesis, we showed that Arabidopsis nucellus cells accumulate autophagosomes before undergoing cell death (Li and Vierstra, 2012).…”
Section: Developmental Progression Of Nucellus Degenerationsupporting
confidence: 74%
“…This suggests that the nucellus plays a role at the boundary between the chalaza and the endosperm during seed development. In some monocotyledonous seeds, the nucellus cells positioned between the vascular bundle and the endosperm, termed the nucellar projection, survive longer than the other nucellus cells and mediate nutrient exchange (Domínguez and Cejudo, 2014). Furthermore, barley (Hordeum vulgare) grains have been shown to accumulate amyloplasts in the degenerating nucellus and nucellar projection and produce a-amylases for its degradation (Radchuk et al, 2009).…”
Section: Developmental Progression Of Nucellus Degenerationmentioning
confidence: 99%
“…During seed germination, aleurone cells hydrolyze carbohydrate reserves and secrete hydrolases to the inner starchy endosperm, which is immediately followed by PCD (Fath et al, 2000). The PCD of aleurone cells is elicited by GA that was secreted by the embryo of the germinated seed so that nutrients in the aleurone layers can finally be completely utilized by the developing embryo (Fath et al, 2001a;Domínguez and Cejudo, 2014). Some putative GA-triggered PCD regulators have been identified in cereal aleurone cells (Fath et al, 2001b).…”
mentioning
confidence: 99%
“…The integuments undergo rapid cell division and expansion to form the seed coat [41], while the proximal region of the nucellus undergoes programmed cell death (PCD) [42]. Sporophyte PRC2 (EMBRYONIC FLOWER2 (EMF2)/VERNALIZATION2 (VRN2)-PRC2) exerts a block on seed coat development before fertilization, and lack of the core PRC2 subunits VRN2 and EMF2 results in dosage-dependent autonomous seed coat development [43].…”
Section: Early Stages In Plant Development and Response To Environmenmentioning
confidence: 99%